2016
DOI: 10.1111/ijcp.12780
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ insight into deprescribing for the multimorbid older individual: a qualitative study

Abstract: Gaining an insight into GPs' current prescribing patterns is important in designing any interventions aimed at reducing inappropriate prescribing. This study highlights the lack of clarity around deprescribing in multimorbidity. The participants' individual responses varied considerably. Deprescribing guidelines may help to clarify evidence based medicine relating to controversial areas and could hence decrease this variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
88
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(88 citation statements)
references
References 68 publications
0
88
0
Order By: Relevance
“…[21][22][23][24][25][26][27][28][29][30] Many of the suggested organizational changes we identified have previously been described, including targeted funding for annual medicines review, computer prompts and alerts, improving information flows between multiple prescribers, improving access to expert advice and user-friendly decision support, increasing availability of non-pharmaceutical alternatives, enhancing patient engagement in medicines management, and more research, education, and training to reduce the uncertainty in practice. [21][22][23][24][25][26][27][28][29][30] The novel contribution of our research lies in its focus on everyday primary care practice, where most ongoing prescribing occurs, and on the sociocultural influences at play-the importance to physicians of maintaining relationships with both patients and colleagues. Study findings draw attention to the need for a change in culture and in the attitudes and behaviors of both patients and physicians as well as a need to "warm the patient up" to the idea of deprescribing; to the possibility that less may be better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25][26][27][28][29][30] Many of the suggested organizational changes we identified have previously been described, including targeted funding for annual medicines review, computer prompts and alerts, improving information flows between multiple prescribers, improving access to expert advice and user-friendly decision support, increasing availability of non-pharmaceutical alternatives, enhancing patient engagement in medicines management, and more research, education, and training to reduce the uncertainty in practice. [21][22][23][24][25][26][27][28][29][30] The novel contribution of our research lies in its focus on everyday primary care practice, where most ongoing prescribing occurs, and on the sociocultural influences at play-the importance to physicians of maintaining relationships with both patients and colleagues. Study findings draw attention to the need for a change in culture and in the attitudes and behaviors of both patients and physicians as well as a need to "warm the patient up" to the idea of deprescribing; to the possibility that less may be better.…”
Section: Discussionmentioning
confidence: 99%
“…Most research has focused on deprescribing in residential care settings, complex case examples, and understanding the views of patients. [21][22][23][24][25][26][27][28][29][30][31] We sought to explore the views of primary care physicians on the barriers to and facilitators of deprescribing in everyday practice to inform the development of an intervention to support safer prescribing.…”
Section: Introductionmentioning
confidence: 99%
“…GPs reported that their decision to stop unnecessary medication was influenced by their perception that specialists would disapprove of them stopping medications. A study in New Zealand investigated GPs' views on deprescribing in multimorbid elderly patients 63. Considerable variation in opinions on deprescribing was observed between GPs, and the authors proposed better guidelines for stopping medicines in order to reduce such variation.…”
Section: Barriers and Facilitators To Deprescribingmentioning
confidence: 99%
“…Another study by Linsky et al identified four factors which include medication knowledge, concerns and importance as well as interest in stopping medication 7. New Zealand general practitioners were included in a study8 which explored their insight into deprescribing for the multimorbid older adult using semi-structured interviews and a hypothetical patient case. This work revealed a lack of clarity around deprescribing.…”
mentioning
confidence: 99%